2002
DOI: 10.1161/01.hyp.0000036455.62159.7e
|View full text |Cite
|
Sign up to set email alerts
|

Programming Effects of Short Prenatal Exposure to Dexamethasone in Sheep

Abstract: Abstract-Recent studies have linked fetal exposure to a suboptimal intrauterine environment with adult hypertension. The aims of the present study were to see whether prenatal dexamethasone administered intravenously to the ewe between 26 to 28 days of gestation (1) resulted in high blood pressure in male and female offspring and whether hypertension in males was modulated by testosterone status, and (2) altered gene expression for angiotensinogen and angiotensin type 1 (AT 1 ) receptors in the brain in late g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
166
3
2

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 179 publications
(177 citation statements)
references
References 50 publications
6
166
3
2
Order By: Relevance
“…Male offspring in this model also demonstrate abnormalities in vascular function in isolated peripheral arteries (26). Blood pressure is also significantly higher in males than females in response to pharmacological levels of dexamethasone administered during early gestation in sheep (27,28). However, moderate protein restriction during gestation in the rat leads to marked increases in blood pressure in male offspring associated with a reduced nephron number (29).…”
Section: Sex Differences In Fetal Programming: Animal Studiesmentioning
confidence: 87%
“…Male offspring in this model also demonstrate abnormalities in vascular function in isolated peripheral arteries (26). Blood pressure is also significantly higher in males than females in response to pharmacological levels of dexamethasone administered during early gestation in sheep (27,28). However, moderate protein restriction during gestation in the rat leads to marked increases in blood pressure in male offspring associated with a reduced nephron number (29).…”
Section: Sex Differences In Fetal Programming: Animal Studiesmentioning
confidence: 87%
“…Previous studies in our laboratory demonstrated that highdose dexamethasone treatment administered to pregnant ewes (240 µg/kg maternal body weight per day), and thus their fetuses, for 2 days, early in pregnancy (26-28 days of gestation), has profound effects on adult cardiovascular function (Dodic et al 1998(Dodic et al , 1999(Dodic et al , 2001b(Dodic et al , 2002a. Also, this 2 day high-dose dexamethasone treatment causes significant changes in gene expression in the kidney, brain and hearts of twin ovine fetuses, killed at 130 days of gestation (Dodic et al 2001a, Hantzis et al 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Note the zona glomerulosa (thin arrow) and zona fasciculata (long arrow) and zona reticularis (thick arrow) H & E x100 the placenta into the foetal circulation and accesses foetal tissues may vary among species (Dodic et al, 2002). The placenta and foetal tissues in more susceptible species would have a greater proportion of glucocorticoid exposure following maternal dexamethasone treatment.…”
Section: Discussionmentioning
confidence: 99%